Morphological Interference of Muna Language Speakers in the Use of Indonesian Language (e-Journal of Linguistics, 2020)
This study aims to examine the Muna language interference on themorphological aspects as a symptom of language that generally occursin bilingual people. The influence of Muna language as a mothertongue and the difference between the morphological system of Munaand Indonesian is very possible for interference. This study wasconducted with 20 participants from different community groups withinthe scope of Kecamatan Mawasangka, Kabupaten Buton Tengah. Thedata were collected using observation method with involved anduninvolved conversation, records and transcribing technique thenanalyzed using padan or Contrastive method to determine the presenceof morphological interference.The result showed that Interference in the aspect of affixation inthis research occurs in the formation of the prefix {ka-}, prefix {kafo-},prefix {ta-}, and confix {ka-...-i}. whereas in the aspect of reduplicationthe interference symptoms are found in the form of partial reduplicationof the Muna language morphological system.Finally, the suggestion in this research that it is expected that thereaders can have better understanding about interference and be morecareful in using language. so as to reduce interference or distortion inlanguage.